Proceso de atención de enfermería en paciente de 73 años de edad con cirrosis hepática. - Carrasco Moreno, Ginger Gabriela (2023)
Cirrhosis is a syndrome that occurs at the stage of all progressive chronic liver diseases. Two very well differentiated phases have been established in natural disease: an asymptomatic phase, which compensated for cirrhosis, and the decompensated phase. In the decompensated phase, it presents clinically with hematemesis or melena due to ruptured esophageal varices, portal gastropathy, encephalopathy, and jaundice. Cirrhosis of the liver and its complications are a clinical picture that carries a considerable risk of disability and with a significant health expense, so preventive measures must be implemented to reduce this pathology, reduce the exacerbation of complications and increase the survival of these patients. Alcohol and the hepatitis C virus are one of the two most frequent factors in our environment. Cirrhosis is characterized by two phases: an asymptomatic phase called compensated liver cirrhosis, and a progressive phase, during which complications occur in different target organs.